Domestic Violence During The Covid-19 Pandemic - Irma Nurbaeti; Tsal Tsa Khairunnisa ((JKG) Jurnal Keperawatan Global, 2022)
Background: Coronavirus-19 (COVID-19) outbreaks experienced by all countries in the world followed by regional and national lockdown. Restriction movement in Indonesia since April 2020 – July 2021 has influenced people’s lives. This situation tends to increase in cases of domestic violence. Methods: Design was quantitatively descriptive research. Population was all married women who living with their partner during the pandemic COVID-19. A number sample of 106 women was recruited by snowball sampling. The study place at Cilegon city Banten Province, Indonesia in June 2021. Instrument for measuring domestic violence was South Asian Violence Screen consist of 11 items; and Scale of Economic Abuse questionnaires Indonesia version consist of 26 items. Data collection was done by online and analysis data performed by frequency distribution Results: The results found that 41 (38.67%) respondents experienced domestic violence during the COVID-19 pandemic. The most forms violence was psychic violence experienced by 32 respondents (30.19%) while 8 respondents (7.55%) experienced more than one violence. Family income (OR= 1.735 (95%CI= 0.697 – 4.322) and spouse’ age (OR= 1.882 (95%CI= 0.529 – 6.697) tend to get domestics violence. Conclusions: Domestic violence during pandemic COVID-19 should be a concern of health workers. Women who are experience domestic violence sometime not dressed up to report. There must be ways and strategies to dare to speak up and report.